Cultivating a sense of ownership over climate change adaptation through the expansion process of local community activities stimulated by urban river restoration in Okazaki City, Japan - Itsumi, Yuta; Chibana, Takeyoshi; Watanabe, Satoshi (Frontiers in Water, 2025)
This study examined how urban river restoration processes can cultivate a sense of ownership and contribute to community-engaged climate change adaptation, focusing on the case of Okazaki City, Japan. The research employed a qualitative approach, analyzing local documents and interviewing ten key volunteers of ONE RIVER, a local citizens’ group. The case study demonstrated that local activities began with utilizing the river area and subsequently expanded to encompass community-based adaptation, including sustainably maintaining the river environment across the entire watershed. Additionally, it was observed that a sense of ownership over climate change adaptation was cultivated in stages through local activities. The volunteer members first recognized the natural appeal of the diverse river ecosystem services with the rich experiences of the natural dynamics, such as seasonal scenery changes and the presence of living organisms. Secondly, they perceived a hidden connection between the river environment and one’s own life by fostering relationships with a diverse range of stakeholders. Our findings indicated that urban river restoration would benefit community-engaged climate change adaptation by revitalizing the connection between urban society and rivers and building reasonable government-community relationships with local participation. The case study also suggested that considering sociocultural differences is crucial for evaluating the benefits of urban river restoration.